Jerome of Stridon and the ethics of literary production in late antiquity - Hunt, Thomas E. (Critical Approaches to Early Christianity Ser., 2020)
"This book becomes legible when light plays across a material substance, be it screen or page. Without the light and without the material, there is no book. To read the book, however, you must perceive meaning in the words before you and in the way that they sit relative to other words, words that are on this page or words that you know and have learned from elsewhere. Without this apprehension - which literary theorists call 'textuality' - there is no book. This book before you is about the interplay between the material and the textual.2 Without the two, it would not exist"--